Hydrologic Impacts of Municipal Wastewater Irrigation to a Temperate Forest Watershed. Issue 4 (1st July 2016) - Birch, Andrew L.; Emanuel, Ryan E.; James, April L.; Nichols, Elizabeth Guthrie
Abstract : Land application of municipal wastewater to managed forests is an important treatment and water reuse technology used globally, but the hydrological processes of these systems are not well characterized for temperate areas with annual rainfall of 1200 mm or greater. This study evaluated the impact of municipal wastewater irrigation to the local water balance at a 3000‐ha land application facility where secondary‐treated wastewater is land applied to a mixed hardwood–pine forest over 900 ha. Stable isotopes of hydrogen ( 2 H) and oxygen ( 18 O), chloride concentrations, and specific conductance were used in combination with hydrometric measurements to estimate the wastewater composition in groundwater, surface water, and at the watershed outlet during dry and wet seasonal periods and during one large rainfall event. Wastewater and water bodies receiving irrigation were found to have significantly higher δ 2 H, δ 18 O, specific conductance, and chloride concentrations. Using these tracers, a two‐component, three‐end member geochemical mixing model estimated mean wastewater compositions in the surficial aquifer receiving irrigation from 47 to 73%. Surface water onsite was found to reflect the high wastewater composition in groundwater. Land‐applied wastewater contributed an estimated 24% of total streamflow, with the highest wastewater compositions in surface water observed during major storm events and at low‐flow conditions. Groundwater and surface water within the watershed were found to have proportionally higher wastewater compositions than expected based on the proportion of irrigation to rainfall received by these areas. Core Ideas: Municipal wastewater irrigation to forested lands can substantially alter the local water cycle. An aquifer receiving spray irrigation was found to be largely composed of wastewater (47–73%). Influence of spray irrigation on receiving water bodies varies with respect to flow conditions.